Endovenous laser ablation with and without high ligation compared to high ligation and stripping for treatment of great saphenous varicose veins: Results of a multicentre randomised controlled trial with up to 6 years follow-up. (February 2016) - Flessenkämper, I; Hartmann, M; Hartmann, K; Stenger, D; Roll, S
Objectives: High ligation and stripping was compared to endovenous laser ablation for the therapy of great saphenous vein varicosity. Long-term efficacy was assessed in terms of avoidance of inguinal reflux and mechanisms of recurrence were investigated. Design: Multicentre, randomised, three-arm, parallel trial. Materials and methods: A total of 449 patients were randomised into three different treatment groups: high ligation and stripping group ( n  = 159), endovenous laser ablation group ( n  = 142; 980 nm, 30 W continuous mode, bare fibre) or a combination of laser ablation with high ligation (endovenous laser ablation group/ high ligation group, n  = 148). Patients were examined clinically and by duplex ultrasound once a year. The primary end point of this study is inguinal reflux at the saphenofemoral junction after 2 years. This paper presents secondary data on sonographically determined inguinal reflux and clinical recurrences in the treated area after up to 6 years of follow-up. Results: Median time to follow-up was 4.0 years; the mean time follow-up 3.6 years. Follow-up rates were: 2 years 74%, 3 years 47%, 4 years 39%, 5 years 36% and 6 years 31%. Most reflux into the great saphenous vein appeared in the endovenous laser ablation group (after 6 years: high ligation/stripping versus endovenous laser ablation p  = 0.0102; high ligation/endovenous laser ablation vs. endovenous laser ablation p  < 0.0002). Furthermore, more refluxive side branches were also observed in the endovenous laser ablation group (after 6 years high ligation/stripping vs. endovenous laser ablation p  = 0.0569; high ligation/endovenous laser ablation vs. endovenous laser ablation p  = 0.0111). In terms of clinical recurrence during the 6 years post therapy, no significant differences between the three treatment groups were observed ( p values from log-rank test: high ligation/stripping vs. endovenous laser ablation p  = 0.5479; high ligation/stripping vs. high ligation/endovenous laser ablation p  = 0.2324; high ligation/endovenous laser ablation vs. endovenous laser ablation p  = 0.0848). The postoperative decline and later development in Class C (clinical etiological anatomical pathological) went parallel in all groups. Conclusions: Clinical recurrence appears with the same frequency in all three treatment groups, but the responsible pathological mechanisms seem to differ. Most reflux into the great saphenous vein and side branches appears after endovenous laser ablation, whereas more saphenofemoral junction-independent recurrences are seen after high ligation/stripping.